Contribution of modelling to the optimization of forming and heat treatment of structural steels - Koutsky, Jaroslav (Communications - Scientific letters of the University of Zilina, 2000)
New laboratory of technological processes modelling, equipped with two Silicon Graphic Indigo R 5000 stations, one 500au DEC OSF/1 station with software systems Forge 2D and 3D, Hypermesh, Systus and Sysweld, was built up at the Department of Material Science and Technology at WBU Plzeň. Some research projects aimed at the modelling and optimization of technological processes, e. g. simulation of cold deformation influence on the structure of P900 steel, or simulation of free forging of shafts manufactured from CrMo steel were carried out. Partial results give a good agreement between experimental results and simulation.